Buddhism and business: merit, material wealth, and morality in the global market economy - Brox, Trine; Williams-Ørberg, Elizabeth (University of Hawaiʻi Press, 2020)
"The objective of the book is to present novel insights into contemporary relations between Buddhism and economy. As an interdisciplinary project, it approaches the study of Buddhism and economy from various perspectives and locations. It provides new empirical research and pushes forward analytical discussions, including: the impact of capitalism and neoliberalism on Buddhist economic relations; the negotiations of morality and value within Buddhist-economic exchanges; how Buddhist networks have risen and spread through global market exchanges and relations; the complex and contentious transformations and ensuing challenges such issues pose to exchange relations and the resulting shifting value regimes. The main argument presented in this book is that Buddhists are necessarily embedded in the global market economy and have various strategies for working within the consumer society and the new spirit of capitalism. Thus, rather than offering normative economic models based upon ideals labelled as Buddhist, the nine chapters constituting this volume turn to how Buddhists and non-Buddhists engage Buddhism within the global market economy."
Bibliografie, Index
Keywords: Konferenzschrift; Kommerzialisierung; Globalisierung; Buddhismus; Wirtschaft